Gaspar Silveira Martins e a Revolução Federalista (1893-1895): que federalismo era esse? - Rossato, Monica (2020)
The present History Doctorate dissertation aimed to investigate the federalism defined in the Federalist Revolution from 1893 to 1895, from the analysis of the political trajectory of Gaspar Silveira Martins, his influence networks and thus verifying the internal divergences in the federalist group, in the context of a political redefinition of the Brazilian State. In this sense, we believe that the federalism consisted of possibilities of responses given by Silveira Martins and the federalist to the restructuration of the Brazilian National State with the recent proclamation of the Republic, such as: the removal of Floriano Peixoto from power by the Revolution and the expansion to other States; the creation of a Provisory Government with the objective of being a Joint Government representing the possibility of the south of Brazil becoming a belligerent State, as a United Republic to the United States of Brazil, with sovereignty to negotiate with other National States of interest and the separation power of Rio Grande do Sul and union with Uruguay and Argentina. The denomination ―federalist‖ embraced political groups aligned with different leaderships that were united in the Federalist Revolution and that diverged in some points regarding the course of the Revolution, identified mainly through intrigues between Demetrio supporters and Gaspar supporters. In this sense, through research in archives and historic sources of countries like Brazil, Uruguay, Argentina, Portugal, France, among others, we mapped the external ties present in the Federalist Revolution, through Gaspar Silveira Martins‘ trajectory, through his experiences while liberal, frontier, exiled from Brazil to Europe (exile), the news and information that spread in Europe and the platine border region, demonstrating that the Revolution was present in international affairs at the end of the 19th century, drawing the interest of European countries and the United States. Thus, the dissertation presents five chapters: in the first, we present the historiographical discussions regarding the Federalist Revolution, federalism and Gaspar Silveira Martins, showing the shallowness with which the federalism of the Revolution was imagined and discussed in the carried out productions. Gaspar Silveira Martins‘ European ties during political exile were developed in the second chapter, followed by his return from Europe, political insertion and involvement in the Revolution, from the perspective of the platine border region, theme of the third chapter. The fourth chapter brought reflections regarding the federalism of Silveira Martins and the Revolution, also listing the federalists‘ internal divergences. Lastly, the fifth chapter consisted of the insertion of the federalists in the post-Revolution, strategies and Silveira Martins‘ performance in regional and national politics, as well as his political legacy and construction of the federalist memory based on his ―Political Testament‖. In this sense, it is worth noticing that the present doctorate dissertation was developed in the History Post-Graduate Program, in the ―Border, Politics and Society‖ Research Group, which counted on the Post-Graduate Students Mobility by the Montevideo Group University Association (AUGM) and on the Sandwich Doctorate scholarship, CAPES Notice 019/2016, from September to December 2017, at the University of Coimbra.